Expression and Regulation of Cornified Envelope Proteins in Human Corneal Epithelium - Tong, Louis (2006)
PURPOSE: Stratified squamous epithelial cells assemble a specialized protective barrier structure on their periphery, termed the cornified envelope. The purpose of this study was to evaluate the presence and distribution of cornified envelope precursors in human corneal epithelium, their expression in human corneal epithelial cell cultures, and the effect of ultraviolet radiation (UVB) and transglutaminase (TG) inhibition on their expression. METHODS: Tissue distribution of small proline-rich proteins (SPRRs) and filaggrin and involucrin was studied in human cornea sections by immunofluorescence staining. Primary human corneal epithelial cells (HCECs) from limbal explants were used in cell culture experiments. A single dose of UVB at 20 mJ/cm(2) was used to stimulate these cells, in the presence or absence of mono-dansyl cadaverine (MDC), a TG inhibitor. SPRR2 and involucrin protein levels were studied by immunofluorescence staining and Western blot analysis. Gene expression of 12 proteins was investigated by semiquantitative reverse transcription–polymerase chain reaction. RESULTS: In human cornea tissue, SPRR1, SPRR2, filaggrin, and involucrin protein expression were detected in the central and peripheral corneal and limbal epithelium. In HCECs, SPRR2 and involucrin proteins were detected in the cytosolic fraction, and involucrin levels increased after UVB. Both SPRR2 and involucrin levels accumulated in the presence of MDC. Nine genes including involucrin, SPRR (types 1A, 1B, 2A, 2B, and 3), late envelope protein (LEP) 1 and 16, and filaggrin were expressed by HCECs. SPRR 4, loricrin, and LEP 6 transcripts were not detected. UVB downregulated SPRR (2A, 2B) and LEP 1 transcripts. CONCLUSIONS: Various envelope precursors are expressed in human corneal epithelium and in HCECs, acute UVB stress differentially alters their expression in HCECs. The expression of envelope precursors and their rapid modulation by UVB supports the role of these proteins in the regulation of ocular surface stress. TG function may be relevant in the regulation of soluble precursors in UVB-stimulated corneal epithelium.